Effects of chronic dietary nitrate supplementation on longevity, vascular function and cancer incidence in rats - Carvalho, Lucas Rannier R.A.; Guimarães, Drielle D.; Flôr, Atalia Ferreira L.; Leite, Ericka G.; Ruiz, Clara R.; de Andrade, Juliana T.; Monteiro, Matheus M.O.; Balarini, Camille M.; Lucena, Ricardo Barbosa de; Sandrim, Valeria Cristina [UNESP]; Lundberg, Jon O.; Weitzberg, Eddie; et al. (Elsevier, 2021)
Rationale: Dietary nitrate and nitrite have a notoriously bad reputation because of their proposed association with disease, in particular cancer. However, more recent lines of research have challenged this dogma suggesting that intake of these anions also possess beneficial effects after in vivo conversion to the vital signaling molecule nitric oxide. Such effects include improvement in cardiovascular, renal and metabolic function, which is partly mediated via reduction of oxidative stress. A recent study even indicates that low dose of dietary nitrite extends life span in fruit flies. Methods: In this study, 200 middle-aged Wistar rats of both sexes were supplemented with nitrate or placebo in the drinking water throughout their remaining life and we studied longevity, biochemical markers of disease, vascular reactivity along with careful determination of the cause of death. Results: Dietary nitrate did not affect life span or the age-dependent changes in markers of oxidative stress, kidney and liver function, or lipid profile. Ex vivo examination of vascular function, however, showed improvements in endothelial function in rats treated with nitrate. Neoplasms were not more common in the nitrate group. Conclusion: We conclude that chronic treatment with dietary nitrate does not affect life span in rats nor does it increase the incidence of cancer. In contrast, vascular function was improved by nitrate, possibly suggesting an increase in health span.
Keywords: Aging; Cancer; Cardiovascular; Health span; Inorganic nitrate; Long-term supplementation; Nitric oxide; Nitrite